Persepsi dan Motivasi Pemangku Kepentingan terhadap Pengembangan Ekowisata Tondok Bakaru - Risal, Darmawan; ., Harsani; ., Harlina; Roynaldi, Hiskia (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 8 No 1 (2021): April 2021, 2021)
Tondok Bakaru Village in Mamasa Regency was designated as a Desa Sadar Wisata in 2019, as an effort to increase the local economy. The purpose of this study to determine the perceptions and motivations of stakeholders towards the development of Tondok Bakaru ecotourism. The phenomenological approach is used to analyze correlations between the proposed development with the economic development, ecology, and socio-culture. Study results are classified based on class intervals listed on the assessment graphs completed with associated descriptions. Notable findings here are as follows. Stakeholder's perception of Tondok Bakaru ecotourism development is on a ‘very agreeable’ scale. This is due to a ‘high desire’ scale expressed by stakeholders to have active roles in the development of ecotourism in Mamasa. Stakeholder motivation towards economic development is also on a ‘high scale’. Many stakeholders also express that it is necessary to improve tourism infrastructures, provide support for orchid cultivation-related business, development of networks for food provision, and other supporting facilities. Aspiration for the development of ecology-based tourism is also on a rather ‘high’ scale, as the concept of Tondok Bakaru ecotourism has not been well-conceived that indeed has disrupted the hydrological system, land conservation, and preservation of flora and fauna. Moreover, aspiration for socio-cultural development is on a ‘very high’ scale. This is influenced by a great concern on the gradual extinction of Tondok Bakaru Village’s socio-cultural assets. Keywords: ecology; economy; ecotourism; stakeholder; socio-culture   Abstrak Desa Tondok Bakaru di Kabupaten Mamasa ditetapkan menjadi Desa Sadar Wisata pada tahun 2019 sebagai upaya peningkatan daya tahan ekonomi lokal. Tujuan penelitian ini adalah untuk mengetahui persepsi dan motivasi pemangku kepentingan terhadap pengembangan ekowisata Tondok Bakaru. Pendekatan fenomenologi digunakan untuk menganalisis persepsi dan motivasi terhadap pengembangan ekowisata yang berkaitan dengan ekonomi, ekologi dan sosial budaya di Tondok Bakaru. Hasil analisis dikelaskan berdasarkan interval kelas pada grafik penilaian dan pemaknaannya diuraikan secara deskriptif kualitatif. Persepsi terhadap pengembangan ekowisata Tondok Bakaru berada pada skala sangat setuju karena didasari oleh adanya keinginan yang tinggi dari pemangku kepentingan untuk berperan aktif pada pengembangan ekowisata di Kabupaten Mamasa. Motivasi pemangku kepentingan terhadap pengembangan ekonomi berada pada skala tinggi. Terbatasnya penunjang ekonomi ekowisata sehingga perlu dilakukan pembenahan infrastruktur, pengadaan inkubasi kelompok usaha budidaya tanaman anggrek, makanan dan penyewaan fasilitas penunjang. Motivasi pada pengembangan ekologi ekowisata pada skala agak tinggi karena konsep pengembangan ekowisata Tondok Bakaru belum tertata dengan baik yang memungkinkan terganggunya sistem hidrologi, konservasi lahan dan  pelestarian flora fauna. Motivasi pada pengembangan sosial budaya berada pada skala sangat tinggi karena dipengaruhi oleh keprihatinan pada asset sosial budaya yang saat ini terancam punah. Kata kunci: ekologi, ekonomi; ekowisata; eemangku kepentingan; eosial budaya